Anti‐A and anti‐B titers in donor plasma, plasma pools, and immunoglobulin final products. Issue 2 (15th May 2015) - McVey, John; Baker, Don; Parti, Rajesh; Berg, Roger; Gudino, Maria; Teschner, Wolfgang
<x xml:space="preserve">Abstract</x> BACKGROUND High‐dose intravenous immunoglobulin (IVIG) treatments are implicated in hemolytic events in some patients receiving treatment. The passive transfer of IgG anti‐A and anti‐B agglutinin is thought to play a role in the development of these events. The purpose of this study was to determine the prevalence of high‐titer IgG anti‐A and anti‐B in plasma donors and investigate if there is any advantage of excluding these donors from the donor pool to limit anti‐A and anti‐B content in IVIG product. STUDY DESIGN AND METHODS IgG anti‐A and anti‐B levels were assessed from group O donor plasma, manufacturing IgG plasma pools, and finished IVIG product (Gammagard Liquid). Antibody level in group O donors was also assessed by sex and age for their relative contribution of antibody to the plasma pool. RESULTS The majority of group O donors (80%) had antibody titers of less than 1000. Of those with titers of at least 1000, theoretical estimates provide further evidence that the effects of high‐titer donors are minimal. Antibody levels in plasma pools both during the manufacturing process and from the final IVIG product also support that anti‐A and anti‐B levels are low. In general, there were more females than males with higher antibody titer levels, with significantly more females than males with anti‐A. CONCLUSION Excluding donors with high anti‐A and anti‐B titers has minimal impact on the finished IVIG product titers due to ABO antibody neutralization and the dilution factor in the manufacturing pool.